An Electromagnetically Controllable Microrobotic Interventional System for Targeted, Real‐Time Cardiovascular Intervention. Issue 11 (18th February 2022) - Hwang, Junsun; Jeon, Sungwoong; Kim, Beomjoo; Kim, Jin‐young; Jin, Chaewon; Yeon, Ara; Yi, Byung‐Ju; Yoon, Chang‐Hwan; Park, Hun‐Jun; Pané, Salvador; Nelson, Bradley J.; Choi, Hongsoo
Abstract: Robotic magnetic manipulation systems offer a wide range of potential benefits in medical fields, such as precise and selective manipulation of magnetically responsive instruments in difficult‐to‐reach vessels and tissues. However, more preclinical/clinical studies are necessary before robotic magnetic interventional systems can be widely adopted. In this study, a clinically translatable, electromagnetically controllable microrobotic interventional system (ECMIS) that assists a physician in remotely manipulating and controlling microdiameter guidewires in real time, is reported. The ECMIS comprises a microrobotic guidewire capable of active magnetic steering under low‐strength magnetic fields, a human‐scale electromagnetic actuation (EMA) system, a biplane X‐ray imaging system, and a remote guidewire/catheter advancer unit. The proposed ECMIS demonstrates targeted real‐time cardiovascular interventions in vascular phantoms through precise and rapid control of the microrobotic guidewire under EMA. Further, the potential clinical effectiveness of the ECMIS for real‐time cardiovascular interventions is investigated through preclinical studies in coronary, iliac, and renal arteries of swine models in vivo, where the magnetic steering of the microrobotic guidewire and control of other ECMIS modules are teleoperated by operators in a separate control booth with X‐ray shielding. The proposed ECMIS can help medical physicians optimally manipulate interventional devices such as guidewires under minimal radiation exposure. Abstract : The clinically translatable, electromagnetically controllable microrobotic interventional system (ECMIS) comprises a microrobotic guidewire capable of active magnetic steering, a human‐scale electromagnetic actuation system, a biplane X‐ray imaging system, and a remote master–slave advancer unit. The ECMIS assists a physician to remotely control microdiameter interventional tools precisely and instantly in a real‐time manner while being protected from ionizing radiation.